Effect of organic acid ligands on nutrient mobilization from volcanic acid soils - SINGH, KALYAN; YOSHIMURA, E; KANAZAWA, K; SUDHAKAR, P C; MORI, S (The Indian Journal of Agricultural Sciences, 2014)
A laboratory study was carried out during 2000 at the Plant Molecular Physiology Laboratory, The University of Tokyo, Japan, to evaluate the effect of increasing concentrations (10, 50, 250 mM) of organic acids (succinate, oxalate, citrate and malate) at differentpH (3, 4,5 and 6) on soil AI, Fe, P, Ca, Mg, Cu and Mn solubility from volcanic acid soils of Japan. Higher solubility values of Al (1.148 and 17.539 ppm), Fe (0.094 and 13.758 ppm) and P (0.052 and 0.565 ppm) were recorded with higher concentration of succinate (250 mM) and oxalate (250 mM) respectively at low pH (3). However, higher solubilization of Mn (0.569 and 0.574 ppm) and Cu (0.0 10 and 0.008 ppm) with the higher concentration of citrate (250 mM) and malate (250 mM) was obtained atpH 5 and 4 respectively. Higher solubility of Ca (5.006 ppm) and Mg (2.063 ppm) were recorded with higher concentration of oxalate (250 mM) at low pH (3), whereas their solubility was almost identical with citrate and malate at low pH (3) but decreased with increasing pH in all the organic acids. Among the nutrients, very high content of AI, Fe and P were mobilized by oxalate, citrate and malate. All the organic acids were almost identical with respect to solubilization ofMg and Mn. Solubility of Ca (0.508 ppm) and Cu (0.0003 ppm) was very low with all organic acids in low concentration (10 mM) at higher pH (6) and succinate almost did not solubilize Cu. Solubility of Al (3.667 mM) and Fe (7.365 mM) increased with increasing shaking hr practically up to 72 hr at low pH (2.5). However, high pH (5.6) and low shaking hr(24) were ideal forMn and Cu. Solubility ofCa and Mg was very little affected by shaking hours.